Policy, objectives, principles and procedures of privatisation in Guyana - Boodhoo, Martin Jagdeo ([s.n.] [S.l.], 1995)
Reviews the background and motivations for the creation of state-owned enterprises whilst at the same time recognising the justifiable objectives of privatisation.